Sufism and Devotion to the Ahl al-Bayt: The Role of the Shādhiliyya Shiddqiyya Order in the Commemoration of Imam Ḥusayn’s Mawlid in Cairo - Muhammad Andhika Adha; Kholid Al Walid; Muhammad Aulia Achyar Nasution (Aqlania, 2025)
This article examines the role of the Shādhilīyyah Shiddqiyyah Sufi Order in the commemoration of the birth of Imam Ḥussain in Cairo, as an expression of Sufism and love for the Ahl al-Bayt within the Sunni Islamic tradition. Using a qualitative approach, this study employs library research and phenomenological hermeneutics to interpret spiritual practices, ritual symbolism, and the Sufi community's response to modern challenges. The findings reveal that the Shādhilīyyah Shiddqiyyah plays a central role in preserving the Maulid tradition through hadrah, awrād, and spiritually rich qasīdah recitations. Beyond the religious dimension, the celebration integrates socio-economic aspects such as seasonal markets (sūq al-mawlid) and mass food offerings (nazr) that enhance community solidarity. Despite criticism from reformist groups, the order demonstrates adaptive capacity by utilizing digital platforms and institutional engagement with religious authorities such as Al-Azhar. The article concludes that Sufi orders are not merely spiritual entities but also dynamic social actors in the landscape of contemporary Islam.